2017
DOI: 10.1088/1361-6579/aa78bd
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface temperature in patients with evaporative and aqueous-deficient dry eyes: a thermographic approach

Abstract: Ocular thermography paves the way to become an effective tool for differentiating between the two different etiologies of dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Galassi et al found lower OST in glaucoma subjects compared to healthy subjects, and the authors suggested that this could be related to hemodynamic alterations in the optic nerve [16]. Other studies have also shown that the OST is lower and the cooling rate faster in DED subjects than in healthy subjects [17][18][19]. As DED is reported in subjects with glaucoma, it is possible that the low OST reported by Galassi is due to the eye drops.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Galassi et al found lower OST in glaucoma subjects compared to healthy subjects, and the authors suggested that this could be related to hemodynamic alterations in the optic nerve [16]. Other studies have also shown that the OST is lower and the cooling rate faster in DED subjects than in healthy subjects [17][18][19]. As DED is reported in subjects with glaucoma, it is possible that the low OST reported by Galassi is due to the eye drops.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, glaucoma group did show shorter FBUT values. In this regard, glaucoma subjects show similar behavior to those with DED [17][18][19]. Further studies that would analyze the thermal characteristics of the ocular surface before and after commencement of glaucoma eye drops are needed to assess if these thermal characteristics are due to the glaucoma itself or by the effects of topical glaucoma medication.…”
Section: B Differences In the Ocular Surface Temperature Dynamics Ofmentioning
confidence: 99%
“…Ocular thermography has been described to be useful for differentiating between aqueous dry eye and evaporative dry eye. 22 It was also applied in patients with dry eye due to dysfunction of lacrimal gland or dysfunction of meibomian glands, or Sjogren's syndrome. 22 25 Thermography was also performed in patients with glaucoma, 26 particularly normal tension glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…22 Evaporative Dry Eye (EDE) patients were found to have a higher initial OST than those with Aqueous Decient Dry Eye (ADDE), suggesting that OST monitoring might be an effective tool to differentiate between different DED aetiologies. 23 An average increase of 0.8 C was observed in the OST of Meibomian Gland Dysfunction (MGD) patients when compared to matched controls. 32 Attempts were made in DED screening by OST measurement.…”
Section: Introductionmentioning
confidence: 99%
“…44 OST has a high potential to be targeted as a parameter for real-time monitoring the ocular physiology. 1,23,25,30,31,45 Contact lenses have recently attracted particular interest to be used as wearable sensing systems for point-of-care medicine. 46,47 In particular, scleral contact lenses are ocular prosthetic devices obtained from rigid polymers with high oxygen permeability for preserving corneal metabolism.…”
Section: Introductionmentioning
confidence: 99%